Effects of aging on the biomechanical properties of the lung extracellular matrix: dependence on tissular stretch - Ulldemolins, Anna; Narciso, Maria; Sanz-Fraile, Héctor; Otero, Jorge; Farré, Ramon; Gavara, Núria; Almendros, Isaac (Frontiers in Cell and Developmental Biology, 2024)
Aging induces functional and structural changes in the lung, characterized by a decline in elasticity and diminished pulmonary remodeling and regenerative capacity. Emerging evidence suggests that most biomechanical alterations in the lung result from changes in the composition of the lung extracellular matrix (ECM), potentially modulating the behavior of pulmonary cells and increasing the susceptibility to chronic lung diseases. Therefore, it is crucial to investigate the mechanical properties of the aged lung. This study aims to assess the mechanical alterations in the lung ECM due to aging at both residual (RV) and functional (FV) lung volumes and to evaluate their effects on the survival and proliferation of mesenchymal stromal cells (MSCs).To this end, the lungs from young (4-6-month-old) and aged (20-24-month-old) mice were inflated with optimal cutting temperature compound to reach FV or noninflated (RV). ECM proteins laminin, collagen I and fibronectin were quantified by immunofluorescence and the mechanical properties of the decellularized lung sections were assessed using atomic force microscopy. To investigate whether changes in ECM composition by aging and/or mechanical properties at RV and FV volumes affects MSCs, their viability and proliferation were evaluated after 72h. Laminin presence was significantly reduced in aged mice compared to young mice, while fibronectin and collagen I were significantly increased in aged mice. In RV conditions, the acellular lungs from aged mice were significantly softer than from young mice. By contrast, in FV conditions, the aged lung ECM becomes stiffer than that of in young mice, revealing that strain hardening significantly depends on aging. Results after MSCs recellularization showed similar viability and proliferation rate in all conditions. Therefore, this data strongly suggests that biomechanical measurements, especially in aging models, should be carried out in physiomimetic conditions rather than following the conventional non-inflated lung (RV) approach. The use of decellularized lung scaffolds from aged and/or other lung disease murine/human models at physiomimetic conditions will help to better understand the potential role of mechanotransduction on the susceptibility and progression of chronic lung diseases, lung regeneration and cancer.